Psychometric properties of the Arabic Stress Numerical Rating Scale (SNRS-11) in adolescents - Sahar Obeid; Rabih Hallit; Diana Malaeb; Fouad Sakr; Mariam Dabbous; Sami El Khatib; Souheil Hallit; Feten Fekih-Romdhane (Scientific Reports)
Abstract Meta-analytic results have revealed a significant influence of stress on a wide array of psychological and behavioral markers, underscoring its considerable clinical importance. Providing a simple and cost-effective tool assessing stress for the Arabic-speaking population would be immensely beneficial. Therefore, our research objective was to examine the psychometric properties of an Arabic version of the Stress Numerical Rating Scale-11 (Arabic SNRS-11), including its reliability, and construct validity. 763 adolescents were recruited during November 2023. An anonymous self-administered Google Forms link was distributed via social media networks. The results of the EFA revealed two factors, which explained 66.43% of the common variance. When adding the SNRS-11, Bartlett’s test of sphericity, χ2(55) = 4127.1, p < 0.001, and KMO (0.88) remained adequate. The two-factor solution obtained explained 63.28% of the variance. The same structure was obtained in both males and females separately. McDonald’s ω and Cronbach’s α were very good for all models. Both PSS and Arabic SNRS-11 scores correlated significantly and positively with each other, as well as with higher depression, anxiety and stress scores. Finally, no significant difference was found between males and females in terms of PSS (27.08 ± 6.43 vs. 27.72 ± 6.06; p = 0.163; Cohen’s d = 0.102) and Arabic SNRS-11 (4.68 ± 2.56 vs. 4.97 ± 2.52; p = 0.125; Cohen’s d = 0.113) scores. The findings indicate that the Arabic SNRS-11 is a cost-effective, valid, and reliable tool for assessing stress. Therefore, it is recommended to use this single item to assess momentary or day-to-day stress among Arabic-speaking adolescents in Arab clinical and research settings. To evaluate the practical effectiveness of the Arabic SNRS-11 and to further enhance the data on its construct validity, future studies should assess the measure in diverse contexts and among specific populations.